Determinan Pemberian Asi Ekslusif pada Bayi di Wilayah Kerja Puskesmas Montasik Kabupaten Aceh Besar Tahun 2025 - Nurmalisa Ananda; Agustina Agustina; Wardiati Wardiati (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Exclusive breastfeeding provides all the nutritional needs necessary for optimal growth during the first six months of life. The percentage of exclusive breastfeeding in the working area of the Montasik Health Center is only 30.5%. The purpose of this study is to determine the determinants of exclusive breastfeeding for babies in the working area of the Montasik Health Center, Aceh Besar Regency in 2025. This study uses an analytical descriptive design with a cross-sectional approach. A sample of 82 mothers with babies was selected through cluster sampling techniques in Mukim Bukit Baro. Data were collected through interviews using questionnaires and analyzed univariate, bivariate, and multivariate using SPSS 24.0. The results showed that only 30.5% of mothers gave exclusive breastfeeding. Most of the respondents had poor knowledge (57.3%), less family roles (52.4%), less supportive maternal behavior (48.8%), did not participate in the Breast Milk Echo (67.1%), had a low income (73.2%), and a small part worked (19.5%). Bivariate analysis showed a significant relationship between family roles (p=0.048), maternal behavior (p=0.013), and income (p=0.000) with exclusive breastfeeding. However, there was no significant relationship with the knowledge, participation of Gema ASI, and maternal work. Multivariate analysis showed only income had a significant effect (p=0.001; OR=8.479), indicating that mothers with sufficient income are 8.479 times more likely to give exclusive breastfeeding. In conclusion, income is the most powerful factor in exclusive breastfeeding. It is recommended that health workers improve education through various media and posyandu activities, and mothers are expected to increase knowledge, positive behavior, family involvement, and participation in the Gema ASI program.